Addressing Foodborne Illness in Côte d’Ivoire: Connecting the Classroom to the Community through a Nonmajors Course-Based Undergraduate Research Experience - Marie A. Smith; Jeffrey T. Olimpo; Karen A. Santillan; Jacqueline S. McLaughlin (Journal of Microbiology & Biology Education, 2022)
ABSTRACT The integration of course-based undergraduate research experiences (CUREs) into science, technology, engineering, and mathematics (STEM) laboratory curricula has provided new avenues to engage students at all levels in discovery-based learning. Empirical research demonstrates that CUREs have the potential to foster students’ development of scientific process and reasoning skills, attitudes, motivations, and persistence in STEM. Yet, these outcomes are largely reported for studies conducted in the United States, Canada, Europe, and Australia. It therefore remains unclear to what extent CUREs are impactful for students enrolled in alternate international university contexts. To address this concern, we conducted a quasi-experimental mixed methods study to investigate the impact of a one-semester food microbiology and public health (FMPH) CURE on nonmajors students’ development of science identity, science communication and process skills, science community values, and science-society perceptions at a private institution in Côte d’Ivoire, West Africa. Content analysis of students’ end-of-semester research poster products and thematic analysis of student responses to post-semester open-ended survey items revealed positive gains with respect to student learning and student perceptions of the relevancy of their research to diverse audiences. Paired t-test analyses of pre-/post-semester closed-ended survey responses likewise indicated significant gains in students’ science identity and science community values development as well as their confidence in handling and treating foods to reduce the bacterial load on those foods. Collectively, these findings suggest that the FMPH CURE was a meaningful and relevant learning experience capable of promoting students’ growth as scientists and scientifically-minded citizens.